A potential role of hydrogen sulfide (H₂S) in the regulation of the Ras-ERK signaling-dependent transcription of DNA methyltransferases - Nikitina, T.A. (Вiopolymers and Cell, 2016)
Ras-ERK cell signaling regulates transcription of DNA methyltransferases (DNMTs). A role of H₂S in regulation of the Ras-ERK signaling activity and DNMTs expression has also been shown. Here we propose a hypothesis that H₂S regulates the Ras-ERK signaling-dependent DNMTs transcription. Oxidative stress, lipid metabolism, protein sulfhydration, nitrosylation and nitration are the main targets of regulation by H₂S. These cell processes are important for the post-translational modifications (PTMs) of the Ras-ERK signaling pathway enzymes. We provide evidence for the dependence of DNMTs transcription on the PTMs of the enzymes of Ras-ERK signaling pathway regulated by H₂S. Існують дані стосовно регуляції Ras-ERK клітинною сигналізацією транскрипції ДНК метилтрансфераз (DNMTs). Також є дані стосовно ролі Н₂S в регуляції активності Ras-ERK сигналізації та експресії DNMTs. В представленому огляді висунута гіпотеза про те, що Н₂S регулює Ras-ERK залежну транскрипцію DNMTs. Було продемонстровано, що окисний стрес , метаболізм ліпі-дів, сульфгідрування та нітрозилювання білків є головними цілями Н₂S-опосередкованої регуляції. Дані клітинні процеси є важ-ливими для після-трансляційної модифікації (ПТМ) ферментів Ras-ERK сигналізації. В огляді представлені дані, що демон-струють залежність транскрипції DNMTs від Н₂S-опосередкованої ПТМ ферментів Ras-ERK сигналізації. Существуют данные о регуляции Ras-ERK клеточной сигнализацией транскрипции ДНК метилтрансфераз (DNMTs). Также есть данные о роли Н₂S в регуляции активности Ras-ERK сигнализации и экспрессии DNMTs. В данном обзоре выдвинута ги-потеза о том, что Н₂S регулирует Ras-ERK-зависимую транскрипцию DNMTs. Было продемонстрировано, что окислительный стресс, метаболизм липидов, сульфгидрирование и нитрозилирование белков является главными целями H₂S-опосрдованной регуляции. Данные клеточные процессы являются важными для пост-транляционной модификации (ПТМ) ферментов Ras-ERK сигнализации. В обзоре представлены данные, демонстрирующие зависимость транскрипции DNMTs от Н₂S-опосредованной ПТМ ферментов Ras-ERK сигнализации.